PENGARUH WORK LIFE BALANCE DAN BURNOUT TERHADAP KEPUASAN KERJA KARYAWAN DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA GALANGAN KAPAL SURABAYA) - Chrisna Ihsannata Suroso; Irma Rustini Aju; Yesica Novrita Devi (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
One of the Surabaya shipbuilding companies is a company that produces ships, along with other supportingcomponents. This shipyard has 22 divisions, one of which is the Technology & Quality Assurance (QA)Division. Not all employees in this division are satisfied with their work. This happens because work targetshave not been achieved, the work environment is less supportive, and the large demands of the job. Thebusy level of work makes employees less optimal in dividing their time between work and family, this canaffect the level of work life balance of employees. Large job demands make employees feel that theirfeelings and thoughts are burdened, which can lead to burnout. Several of these factors can be linked toemployee engagement in employees. Employee engagement needs to be carefully considered, so thatemployees have a feeling of participating in their work. This research used a sample of 46 employees, andthe data was processed using the Partial Least Square (PLS) method. In the test results, it was found thatwork life balance had no effect on job satisfaction with a value of 0.167<0.05, burnout had an effect on jobsatisfaction with a value of 0.041<0.05, work life balance had an effect on job satisfaction with employeeengagement as an intervening variable with a value of 0.016<0.05, burnout influences job satisfaction withemployee engagement as an intervening variable with a value of 0.04<0.05.